ANTIMICROBIAL STEWARDSHIP: KNOWLEDGE, ATTITUDE AND PERCEPTIONS OF AGRICULTURAL SCIENCE STUDENTS, IN A TERTIARY UNIVERSITY IN SOUTH AFRICA (Proceedings of the International Conference on Public Health, 2025)
The excessive use of antimicrobials in agriculture significantly contributes to the development of antimicrobial resistance in human and animal health, and impacts food safety, food security, and the economy of the country. In the fight against antimicrobial resistance equipping future professionals and developing a coordinated intervention designed to improve use of antimicrobial agents is essential in the agriculture sector. The aim of this study was to investigate the knowledge, attitudes, and perceptions of final-year students enrolled in plant-related agricultural science programs at the University in South Africa on antimicrobial stewardship. A descriptive cross-sectional study design using a self-administered questionnaire was utilized. The participants were final-year students enrolled in agricultural science programs specializing in plant-related studies. Data was analysed using the IBM SPSS version 28 statistical software.  A total of 28 participants which was a 68.29% response rate was attained. The participants demonstrated a solid understanding of antimicrobial stewardship as they all correctly described its role; however, some misconceptions regarding important concepts were observed. The participants demonstrated a positive attitude towards antimicrobial resistance prevention, however, 28.6% felt it is an extra burden. They also recognized the global seriousness of antimicrobial resistance and its threat to them and their families, however, only 32.1% of them felt adequately prepared to contribute to the fight against it. Furthermore, there was moderate, positive association between the participants' overall AMS knowledge and their perception. The association between participants' perceptions and attitudes was found to be moderate and negative. No association was found between their AMS knowledge and their attitude. This study underscores the need to focus on perceptions and attitudes in the preparation of future agricultural science professionals on antimicrobial stewardship.
Keywords: antimicrobial stewardship; plant health; agricultural science; antimicrobial resistance